2023
DOI: 10.3389/fmicb.2022.1101144
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in silico assessment of probiotic and functional properties of Bacillus subtilis DE111®

Abstract: Bacillus subtilis DE111® is a safe, well-tolerated commercially available spore-forming probiotic that has been clinically shown to support a healthy gut microbiome, and to promote digestive and immune health in both adults and children. Recently it was shown that this spore-forming probiotic was capable of germinating in the gastrointestinal tract as early as 3 h after ingestion. However, a better understanding of the mechanisms involved in the efficacy of DE111® is required. Therefore, the present investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 79 publications
1
10
0
1
Order By: Relevance
“…B. coagulans CGI314 demonstrated superior stability over L. rhamnosus GG and L. fermentum ME-3 ( Figure 3 ). These findings are in line with previous data investigating the stability of other members of Bacillus species in different food and beverage with relevant temperature stability testing ( Khokhlova et al, 2023 ; Mazhar et al, 2023 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…B. coagulans CGI314 demonstrated superior stability over L. rhamnosus GG and L. fermentum ME-3 ( Figure 3 ). These findings are in line with previous data investigating the stability of other members of Bacillus species in different food and beverage with relevant temperature stability testing ( Khokhlova et al, 2023 ; Mazhar et al, 2023 ).…”
Section: Discussionsupporting
confidence: 92%
“…Oxidants, such as reactive oxygen species (ROS) and reactive nitrogen species (RNS), can generate free radicals that can cause severe oxidative damage to cellular lipids, membranes, proteins, and DNA ( Mazhar et al, 2023 ; Simon et al, 2023b ). Antioxidants can scavenge these free radicals and prevent cellular oxidative stress by enzymatic and non-enzymatic mechanisms ( Valko et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, glutathione peroxidase ( bsaA ) is known to protect cells from oxidative stress by reducing hydrogen peroxide to water ( Lubos et al, 2011 ). Previous studies have also reported the presence of multiple genes encoding catalase and peroxidase in the genome of Bacillus subtilis DE111, a safe commercial probiotic ( Mazhar et al, 2022 ). In this study, we found that Bacillus velezensis TS5 contains multiple genes encoding both glutathione peroxidase, catalases, peroxidases, and thioredoxin which further validated its antioxidant properties ( Supplementary Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus subtilis ( B. subtilis ) has long been used as a probiotic for the treatment of intestinal diseases in humans and animals, and in recent decades has been developed for use as animal feed enhancers and antifungal biocontrol agents ( Joshi et al, 2008 ; Harwood et al, 2018 ; Rhayat et al, 2019 ). B. subtilis can also produce a range of secondary metabolites, including polyketides, terpenes and siderophores, or ribosomally and non-ribosomally synthesized peptides to exert their inhibitory effect on bacterial pathogens in vitro and in vivo ( Nannan et al, 2021 ; Ji et al, 2022 ; Mazhar et al, 2022 ; Qiu et al, 2022 ). Recently, it was shown that the secondary metabolites of B. subtilis has antiviral activity.…”
Section: Introductionmentioning
confidence: 99%